Protected area asset stewardship - Jepson, P; Caldecott, B; Schmitt, S; de Carvalho, S; Correia, R; Malhado, A; Gamarra, N; Bragagnolo, C; Ladle, R (Elsevier, 2017)
Protected areas (PAs) are the main strategy to conserve natural values and reduce biodiversity loss. However, with increasing global food requirements, using land for protecting landscapes and species is becoming increasingly difficult to justify. Here, we argue that framing PAs as spatial assets provides an ideal platform for generating investment and increasing their political/cultural resilience. Specifically, we define and characterize PAs in terms of their biophysical, human, infrastructure, institutional and cultural assets, making explicit the forms of value they create and for whom, and identifying types of investment needed to generate value in the medium and long term. These assets can be protected, managed and/or invested in to generate (monetizable and non-monetizable) forms of value. They can also be at risk from a variety of factors. Building on contemporary conservation policy, our asset framework provides an innovative approach to the development and management of PAs in the 21st Century.